Economic growth: contribution y resources share - Villalobos Céspedes, Daniel (2019)
This research seeks to contribute to the economic growth theory. It proposes a logical-mathematical conceptual analysis, generating a rigorous and useful model of economic growth. The starting point is the cost of production from which the elasticity of resources’ composition, which includes the elasticity of capital-labor composition of the production process, is among the fundamental results. It was unveiled the contribution and share of resources in the cost and on production growth. From that dynamic, resources as the profit and the rate of profit appear as labor and capital contribution. It is revealed a residue which originates in investment and is reflected by the production and profit. To appraise the model, within relevant limits, we found useful capital, labor, and production indexes of the United States’ Manufacture (1899-1922) provided by Cobb and Douglas (1928) in A Theory of Production.